2002
DOI: 10.1038/sj.onc.1205163
|View full text |Cite
|
Sign up to set email alerts
|

Complex regulatory mechanisms of telomerase activity in normal and cancer cells: How can we apply them for cancer therapy?

Abstract: Telomerase activation is observed in almost 90% of human cancers but not in normal tissues of somatic origin and thus is a critical step for multistep carcinogenesis. A more thorough understanding of telomerase regulation may provide not only a molecular basis of cancer progression but also as a way to manipulate telomerase activity as a potential therapeutic modality. Recent progress in studies on telomerase regulation has shown that telomerase activation is achieved at various steps, including transcriptiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
115
0
12

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 80 publications
2
115
0
12
Order By: Relevance
“…Researchers have been investigating the regulatory mechanisms of telomerase that determine the immortality of cancer cells. Although the increasing evidences obtained to date have indicated that telomerase regulation is complex (Aisner et al, 2002;Katakura et al, 2005), significant research efforts have been focused on the transcriptional regulation of the human telomerase reverse transcriptase (hTERT) gene (Kyo and Inoue, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have been investigating the regulatory mechanisms of telomerase that determine the immortality of cancer cells. Although the increasing evidences obtained to date have indicated that telomerase regulation is complex (Aisner et al, 2002;Katakura et al, 2005), significant research efforts have been focused on the transcriptional regulation of the human telomerase reverse transcriptase (hTERT) gene (Kyo and Inoue, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The differential expression of telomerase in most malignant cells makes it an attractive target for cancer therapy (Mokbel, 2003;Shay and Wright, 2003); however, recent progress in studies on telomerase regulation has shown that telomerase activation is achieved by a process involving various steps including transcriptional and post-transcriptional levels of hTERT gene (Kyo and Inoue, 2002). An alternate splicing of hTERT transcript is one of the regulatory mechanisms of telomerase activity (Ulaner et al, 1998).…”
mentioning
confidence: 99%
“…8 The vast majority of malignant tumors express telomerase whereas most normal cells do not. 9,10 Therefore, telomerase may be a good candidate for targeted therapy. Three components of the human telomerase have been identified: hTR, the telomerase-associated protein TEP1, and hTERT.…”
Section: Discussionmentioning
confidence: 99%